Investigating the Viability of Rubber Crumbs from Waste Tyres as Partial Replacement for Coarse Aggregates in Concrete - Uche, Chikadibia Kalu Awa; Eze, Val Hyginus Udoka; Kitaata, Paul; Chranimah, Muhereza; Ukagwu, Kelechi John; Barah, Obinna Onyebuchi; Edozie, Enerst (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The number of waste tyres is on the increase, because of the growing use of transport vehicles. Almost one trillion waste tyres are generated in the world annually. Established methods of disposal, recycling and re-use of waste tyres have failed to keep pace with generation, proven to be ineffective, cost-intensive and in some cases environmentally unsustainable. This study aims to investigate the effects of utilizing crumbs from discarded rubber as a partial replacement for coarse aggregates in concrete. Rubber crumbs of 10 – 20mm nominal size were produced manually from waste tyres. The rubber crumbs were used to replace 10%, 20% and 30% of coarse aggregates in design concrete of 20N/mm2 target compressive strength. The effects of this material on the slump, water absorption and compressive strength of concrete were examined. The inclusion of rubber crumbs resulted in a decline in the slump of concrete up to 10% relative to the control specimen. Water absorption increased marginally at 10% replacement compared to the control specimen and recorded a maximum value of 0.77% with 30% replacement after 28 days of curing. The compressive strength of the concrete was negatively affected by the rubber crumbs. The maximum value of 13.9N/mm2 was attained at 10% replacement after 28 days of curing. Rubberized concrete with 10% replacement of coarse aggregates can be used for non-structural concrete members such as roof slabs, non–load–bearing partition walls, and roadside barriers. Chemical treatment of rubber crumbs to improve surface adhesion properties should be encouraged.